2014
DOI: 10.2174/221279680801141112094818
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetic Pathways to Glycosidase Inhibitors

Abstract: Glycosidase inhibitors are important compounds that can interfere with several biosynthetic processes including N-linked glycosylation and the biosynthesis of several glycoproteins. Understanding the biogenesis of naturally occurring glycosidase inhibitors would be a crucial step towards the chemical synthesis of analogues of choice. This review focuses on the current knowledge regarding the biosynthesis of a series of polyhydroxylated saturated nitrogen heterocycles including nojirimycin and swainsonine among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Thee arly to mid-1970s was clearly ah ive of incredible activity and ingenuity the accumulation of which eventually both led to the invention of the LIB,w hich has revolutionized our lives,a nd is connected to SSBs which in 2019 were highlighted as one of the top ten emerging innovations in chemistry by the International Union of Pure and Applied Chemistry (IU-PAC). [16] The Birth of The "Rocking-Chair Battery" Concept in the Late 1970s…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Thee arly to mid-1970s was clearly ah ive of incredible activity and ingenuity the accumulation of which eventually both led to the invention of the LIB,w hich has revolutionized our lives,a nd is connected to SSBs which in 2019 were highlighted as one of the top ten emerging innovations in chemistry by the International Union of Pure and Applied Chemistry (IU-PAC). [16] The Birth of The "Rocking-Chair Battery" Concept in the Late 1970s…”
Section: Angewandte Chemiementioning
confidence: 99%
“…1-Deoxynojirimycin (1) is a piperidine alkaloid found in various plants such as Commelina communis, and in the Streptomyces and Bacillus bacteria. 52,53 It has antihyperglycemic, anti-obesity, and antiviral activities. 54 It has been reported to be effective against hepatitis, 55 influenza 56 and HIV.…”
Section: -Deoxynojirimycinmentioning
confidence: 99%
“…Biosynthetic studies, conducted by feeding 14 C-lysine to R. leguminicola cultures and recovering 14 C-slaframine, have demonstrated that slaframine is derived from lysine (Figure 2 D) ( 18 , 37 ), which is converted into pipecolic acid (Figure 2 E) ( 37 ). The incorporation of 14 C into slaframine decreased if non-radioactive pipecolic acid was fed along with 14 C-lysine, an indication that pipecolic acid was a more immediate precursor of slaframine than lysine ( 37 , 38 ). Pipecolic acid is a precursor of various microbial secondary metabolites ( 39 ).…”
Section: Alkaloid Production and Physiological Effectsmentioning
confidence: 99%